2023
DOI: 10.1186/s12934-023-02034-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of itaconic acid production on Neurospora crassa in consolidated bioprocessing of cellulose

Abstract: A system for itaconic acid synthesis from cellulose by Neurospora crassa was established, resulting in the highest yield of itaconic acid was 354.08 + 35.99 mg/L. Meanwhile, cellulase activity increased significantly, without any strain modifications for improved cellulase production. Multi-omics analyses showed that itaconic acid synthesis reduced energy production, leading to decreases in trehalose, cell wall, fatty acids synthesis and downregulations in MAPK signaling pathway, cell cycle and meiosis. More i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 41 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…To further increase the content of the precursor cis-aconite acid in the cytoplasm, the cis-aconite transporter MTTA from Aspergillus terreus was expressed on the basis of constructing the rGS. Our previous studies have shown that MTTA expression could significantly increase itaconic acid production [ 12 ]. Figure 4 E shows that the titer of strain PMF–CAD–MTTA was 356.4 mg/L, and the highest titer of PMF–CAD–MTTA–rGS was 637.2 mg/L, indicating that the rGS could further enhance the itaconic acid titer on the basis of the expression of MTTA.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To further increase the content of the precursor cis-aconite acid in the cytoplasm, the cis-aconite transporter MTTA from Aspergillus terreus was expressed on the basis of constructing the rGS. Our previous studies have shown that MTTA expression could significantly increase itaconic acid production [ 12 ]. Figure 4 E shows that the titer of strain PMF–CAD–MTTA was 356.4 mg/L, and the highest titer of PMF–CAD–MTTA–rGS was 637.2 mg/L, indicating that the rGS could further enhance the itaconic acid titer on the basis of the expression of MTTA.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of itaconic acid weakened the TCA cycle and electron transport chain, which reduced the productivity of the entire system. Under the condition of low energy, the cellulase system was adjusted accordingly, which increased the synthesis of LPMOs related enzymes, and thus improved the overall cellulase activity [ 12 ]. Strain PMF–CAD–MTTA–TrCBH2 was constructed to further expressed the cellobiohydrolase 2 in the strain PMF–CAD–MTTA to improve the overall cellulase activity, thereby increasing the concentration of itaconic acid.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, Aspergillus oryzae is a convenient host, because it is a GRAS (generally regarded as safe) organism and produces none or very few own polyketides. It has been used to decipher the alternariol biosynthesis (Wenderoth et al, 2019) and more recently for the production of basidiomycete polyketides (Han et al, 2023).…”
Section: S M Mining and " B I Osynthe Ti C Dark Mat Ter "mentioning
confidence: 99%